PIX solução tecnológica de inclusão financeira (Research, Society and Development, 2021)
The article investigated the results of the PIX since its emergence in November 2020 recording the economic advances to then describe the financial inclusion that the PIX has already enabled, as well as the adjustments in the planning of the tool that are being developed for a better adequacy of the same. The work used the tools of bibliographic research and data analysis. It was concluded that the need for democratization of financial systems to promote social and economic development took its first steps with PIX and is already a reality; and adjustments were and will be made to ensure that the system is not used for illicit purposes. The contribution of this study is to provide an evaluation in relation   to the functioning ofthe PIX tool and to investigate its developments in the field of social and economic development and what effects have been observed so far after the introduction of the payment system in the Brazilian market.